2016
DOI: 10.1590/0103-6440201600602
|View full text |Cite
|
Sign up to set email alerts
|

Ions Release and pH of Calcium Hydroxide-, Chlorhexidine- and Bioactive Glass-Based Endodontic Medicaments

Abstract: This study evaluated pH and release of calcium, sodium and phosphate ions from different medications in human dentin. Fifty premolars were prepared and randomly divided into groups: (CHX) - 2% chlorhexidine gel; (CHX + CH) - CHX + calcium hydroxide PA; (CH) - CH + propylene glycol 600; (NPBG) - experimental niobium phosphate bioactive glass + distilled water; (BG) - bioactive glass (Bio-Gran) + distilled water. The specimens were immersed in deionized water and the pH variations were measured. The quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
(28 reference statements)
1
18
0
2
Order By: Relevance
“…Also, it showed the mineral enrichment efficacy [33] . This was in consonance with Carvalho et al [34] who reported that bioactive glasses presented an alkaline pH immediately in the first 10 min, and over the course of 7 days tended to neutralize. Also, in the first 10 min, Bioglass released more calcium, but from 24 h on, this release was decreased and ceased on the 14 th day.…”
Section: Ph and Ca 2+ Releasesupporting
confidence: 90%
“…Also, it showed the mineral enrichment efficacy [33] . This was in consonance with Carvalho et al [34] who reported that bioactive glasses presented an alkaline pH immediately in the first 10 min, and over the course of 7 days tended to neutralize. Also, in the first 10 min, Bioglass released more calcium, but from 24 h on, this release was decreased and ceased on the 14 th day.…”
Section: Ph and Ca 2+ Releasesupporting
confidence: 90%
“…The material is mainly composed of sodium oxide, which stimulates the formation of mineralized tissue. 32,33,34,35,36 Calcium and sodium ion release increases the pH of the dental environment and prohibits bacterial viability.…”
Section: 30mentioning
confidence: 99%
“…The different mechanism of ions release between Ca(OH) 2 and bioactive glasses can support the current results where we found a higher dentinal MH when bioactive glasses were in contact with dentin. In a previous study [23], it was shown that NbG and 45S5 release calcium ions, decreasing the amount over time (0 to 14 days), similarly to what occurs with Ca(OH) 2 . If we considered this fact alone, we should expect a reduction in dentinal MH for samples treated with bioactive glasses, in the same manner than that occurred for the samples treated with Ca(OH) 2 .…”
Section: Discussionmentioning
confidence: 80%
“…We obtained NbG by the fusion of chemical precursors in an electric furnace, according to previous studies [22,23]. The composition of the NbG was 44 wt% Nb 2 O 5 , 3 wt% P 2 O 5 , 21 wt% CaO, and 2 wt% Na 2 O, and 45S5 45 wt% SiO 2 , 24.5 wt% CaO, 24.5 wt% Na 2 O, and 6 wt% P 2 O 5 .…”
Section: Methodsmentioning
confidence: 99%